A comparison study of headache characteristics and headache-associated quality-of-life of COVID-19 and non-COVID-19 patients - Endang Mutiawati; Raisha Fathima; Syahrul Syahrul; Nasrul Musadir; Hendrix Indra Kusuma (Narra Sains Indonesia, 2022)
Headache is prevalent in coronavirus disease 2019 (COVID-19) patients. The main objective of this study was to compare the characteristics of COVID-19-associated headache to non-COVID-19 headache. The quality-of-life (QoL) and its associated determinants between COVID-19 and non-COVID-19 patients were also compared. A cross-sectional study was conducted in Banda Aceh, Indonesia. Headache and QoL were assessed using the International Classification of Headache Disorders, version 3 (ICHD-3), and the 36-item Short Form Health Survey (SF-36), respectively. Factors associated with poor QoL in COVID-19 and non-COVID-19 patients were examined using logistic regression. A total of 356 headache patients were included: 215 COVID-19 and 141 non-COVID-19 patients. Our data suggested that the headache in COVID-19 patients was bilateral; pain centered on one specific area with a pulsating or pressing sensation; pain intensity ranging from moderate to severe; and the frequency ranging from more than twice per week to every day. Non-COVID-19 headache was bilateral; pain centered on one side of the head resembling a migraine with pulsating or pressing sensation; mild to moderate pain intensity; and the frequency of one or two times per month. In COVID-19, low QoL was associated with unemployment status, having non-health-related jobs, having used painkillers to reduce the pain, having long duration of headache, having more frequency of attacks, and having headaches that were worsened by activities or light, and having additional symptom during a headache attach. In non-COVID-19 patients, poor QoL was associated with the use of painkillers, long duration of headache, and having conditions that aggravate the headache. To prevent long-term effects of headache associated with COVID-19, studies exploring the photobiology of headache are needed, along with the necessity of having standardised guideline on headache prevention.